Eugenol restricts Cancer Stem Cell population by degradation of β-catenin via N-terminal Ser37 phosphorylation-an in vivo and in vitro experimental evaluation. (25th January 2020) - Choudhury, Pritha; Barua, Atish; Roy, Anup; Pattanayak, Rudradip; Bhattacharyya, Maitree; Saha, Prosenjit
Abstract: Eugenol a phenylpropanoid, predominantly found in clove is a very common spice in daily cuisine. It already reported to have anti-breast cancer activity. In this study, the effect of eugenol on CSC (Cancer Stem Cell) markers and its main regulator β-catenin both in vivo Ehrlich Ascites Carcinoma (EAC) cell line and in vitro MCF-7 cell line was investigated with that of the untreated group. The therapeutic doses were found to significantly induce apoptosis leaving normal mice and cells unaffected. The in-depth analysis revealed the downregulation of β-catenin thereby facilitating its degradation by N-terminal phosphorylation of Ser37 residue. Significant downregulation of various CSC markers was also observed in vivo after eugenol treatment those are regulated by the intracellular status of β-catenin. These findings were validated by the effect of eugenol on the formation of the secondary sphere in vitro . Notable downregulation of the enriched stemness of secondary mammosphere was detected by the significantly decreased percentage of CD44 + /CD24 -/low population after eugenol treatment along with their distorted morphology and smaller the number of spheres. The underlying mechanism revealed significant downregulation of β-catenin and the set of CSC markers along with their reduced mRNA expression in secondary sphere culture. Therefore, it can be concluded from the study that eugenol exerts its chemotherapeutic potential by impeding β-catenin nuclear translocation thereby promoting its cytoplasmic degradation as a result stemness is being suppressed potentially even if in the enriched state. Therefore the study contributes to reduce the cancer-induced complications associated with the CSC population. This will ultimately confer the longer and improved patient's life. Graphical abstract: Image 1 Highlights: Establishing β-catenin as a novel druggable target of eugenol on cancer cell lines. Restriction of β-catenin nuclear translocation upon eugenol treatment. Increased N-terminal phosphorylation hence degradation of β-catenin by eugenol. Downregulation of related CSC markers in stemness enriched spheroid culture.